Occupational and patient exposure as well as image quality for full spine examinations with the EOS imaging system. Issue 6 (2nd May 2014) - Damet, J.; Fournier, P.; Monnin, P.; Sans‐Merce, M.; Ceroni, D.; Zand, T.; Verdun, F. R.; Baechler, S.
Abstract : Purpose: EOS (EOS imaging S.A, Paris, France) is an x‐ray imaging system that uses slot‐scanning technology in order to optimize the trade‐off between image quality and dose. The goal of this study was to characterize the EOS system in terms of occupational exposure, organ doses to patients as well as image quality for full spine examinations. Methods: Occupational exposure was determined by measuring the ambient dose equivalents in the radiological room during a standard full spine examination. The patient dosimetry was performed using anthropomorphic phantoms representing an adolescent and a five‐year‐old child. The organ doses were measured with thermoluminescent detectors and then used to calculate effective doses. Patient exposure with EOS was then compared to dose levels reported for conventional radiological systems. Image quality was assessed in terms of spatial resolution and different noise contributions to evaluate the detector's performances of the system. The spatial‐frequency signal transfer efficiency of the imaging system was quantified by the detective quantum efficiency (DQE). Results: The use of a protective apron when the medical staff or parents have to stand near to the cubicle in the radiological room is recommended. The estimated effective dose to patients undergoing a full spine examination with the EOS system was 290 μ Sv for an adult and 200 μ Sv for a child. MTF and NPS are nonisotropic, with higher values in the scanning direction; they are in addition energy‐dependent, but scanning speed independent. The system was shown to be quantum‐limited, with a maximum DQE of 13%. The relevance of the DQE for slot‐scanning system has been addressed. Conclusions: As a summary, the estimated effective dose was 290 μ Sv for an adult; the image quality remains comparable to conventional systems.